Reviewing Mindfulness-Based Interventions for Suicidal Behavior. Issue 4 (1st October 2016) - Chesin, Megan; Interian, Alejandro; Kline, Anna; Benjamin-Phillips, Christopher; Latorre, Miriam; Stanley, Barbara
Abstract : This article describes the rationale for using mindfulness-based interventions (MBIs) to prevent suicidal behavior in high suicide-risk individuals. A narrative review of studies testing the feasibility of MBIs with individuals at risk for suicidal behavior and the effectiveness of MBIs for reducing suicidality was conducted. Studies testing the effectiveness of MBIs for reducing deficits specific to suicide attempters among depressed individuals were also reviewed as were studies examining moderators of MBI treatment adherence and effectiveness to the extent that these might suggest possible limitations to using MBIs with high suicide-risk individuals. Findings from the handful of available studies support targeting suicidal ideation with MBI. Additional studies show deficits associated with suicide attempt, namely attentional dyscontrol, problem solving deficits, and abnormal stress response, are improved by MBI and thus strengthen the rationale for using MBIs with high suicide-risk individuals.